New laterite-based geopolymer foam resistance under drastic conditions: A comparative study with a metakaolin model. Issue 8 (15th April 2023) - Joelle Nadia, Nouping Fekoua; Gharzouni, Ameni; Nait-Ali, Benoit; Ouamara, Lila; Ndassa, Ibrahim Mbouombouo; Bebga, Gouet; Elie, Kamseu; Rossignol, Sylvie
Abstract: The valorization of local materials in public building construction in emerging countries is a necessity from a sustainable development perspective. In Cameroon, laterite is an abundant and easily accessible local resource that can be used for the development of light and insulating materials, which until now have been made from metakaolin. Moreover, since metakaolin is not easily accessible in Cameroon, it would be interesting to compare to a model mixture based on metakaolin and hematite. The objective of this study is related to the feasibility and characterization of geopolymer foams based on laterite or on a model mixture (metakaolin-hematite) in different drastic conditions, such as fire resistance and freeze‒thaw cycles. The geopolymer foams were synthesized from a calcined laterite or metakaolin-hematite mixture, an alkaline silicate solution, a surfactant and metallic aluminum powder and then placed in an oven at 70 °C for 24 h. Structural data (X-ray diffraction) as well as determination of thermal conductivity and mechanical strength data of the foams were evaluated. The results show that the laterite and metakaolin-hematite mixture allows the elaboration of geopolymer foam, which is characterized by a low thermal conductivity (90 mW/(m. K)) and can be used as insulating materials. The freeze‒thaw treatment does not affect the thermal and mechanical properties. The treatment at 1175 °C slightly improves the mechanical strength and the thermal conductivity, leading to a good application of these materials.